(3GdJYdje ddLejY Jbjje YGe (B2000(3, GdJbQjQ GdhWfjs - (3HYGUjQj, Sdhis ((3HjQhJs (3cdjI GdJQHjIs, 2000)
(3gh GdJbQjQ GdPj hVYJg dLfI hWfjI dHfGfjI dJbOjeg Edi eDJeQ GdJYdje ddLejY GdPj YbO dGMbkG aj GdbGgQI GdYGe (B2000. (3jTJed GdJbQjQ Ydi ebOeI hKdGKI CbSGe hedGMb, jJfGhd GdbSe GdChd ZGjGJ GdJYdje ddLejY aj eMGhQg GdSJI, hNWW GdYed, hGdJbOjQGJ GdJj MOKJ efP GdYGe (B1990 (3CeG GdbSe GdKGfj ajJYdb HJbjje aYGdjI GdfXGe GdJQHhj, hjJfGhd GdbSe GdKGdK GdGSJQGJjLjGJ GdeSJbHdjI, hJVe GdedGMb HYV GdeYWjGJ GdCSGSjI eMGhQ GdJYdje ddLejY GdSJI GdJj Uee GdJbQjQ Ydi VhFgG gj(B: (3QYGjI GdWahdI GdeHcQI hJfejJgG, GdJYdje GdGHJOGFj, GdJMUjd GdYdej heNQLGJg, GdbQGQ (B...... (3GdcHGQ, GdJOQjH Ydi GdegGQGJ GdegfjI, GdJYdje ef CLd MjGI CaVd(B.s
(3GdfhY (B: (3cJGHs
Keywords: Education for All; Education pour tous; (3GdJYdje ddLejYs